2019
DOI: 10.1177/2192568218818164
|View full text |Cite
|
Sign up to set email alerts
|

Screw-Related Complications After Instrumentation of the Osteoporotic Spine: A Systematic Literature Review With Meta-Analysis

Abstract: Study Design: Systematic literature review with meta-analysis. Objective: Osteoporosis is common in elderly patients, who frequently suffer from spinal fractures or degenerative diseases and often require surgical treatment with spinal instrumentation. Diminished bone quality impairs primary screw purchase, which may lead to loosening and its sequelae, in the worst case, revision surgery. Information about the incidence of spinal instrumentation-related complications in osteoporotic patients is currently limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 73 publications
3
56
1
Order By: Relevance
“…Reduced bone density is known to be a major contributor to worse clinical outcomes after spinal fusion. [ 25 ] Interestingly, reduced bone mineral density did not seem to have an effect on the development for JK/JF in our study. Since DEXA scans were not available for all patients in our study, we chose to use the mean HU measured in the LIV on preoperative CT as a surrogate.…”
Section: Discussioncontrasting
confidence: 55%
“…Reduced bone density is known to be a major contributor to worse clinical outcomes after spinal fusion. [ 25 ] Interestingly, reduced bone mineral density did not seem to have an effect on the development for JK/JF in our study. Since DEXA scans were not available for all patients in our study, we chose to use the mean HU measured in the LIV on preoperative CT as a surrogate.…”
Section: Discussioncontrasting
confidence: 55%
“…Posterior short segment fixation including the fractured vertebral has been widely applied for thoracolumbar fractures, this method can reduce the operation time and bloods loss, preserve motion segments compared to long-segment posterior fixation, and provide greater mechanical strength to prevent early implant failure compared with traditional 4-screws short-segment posterior fixation [ 17 ]. However, diminished bone quality in osteoporotic vertebral impairs primary screw purchase, and screw loosening incidences will be considerably higher than with normal bone mineral density, cement augmented screw fixation may reduce loosening risks [ 18 ]. Kim et al demonstrated cement augmented six screw fixation including the fractured vertebral is satisfactory in maintaining the deformity correction for the patients with severe osteoporotic burst fractures, the average amount of correction loss of the kyphotic was 2.0 degrees 15 months post-operation, and there were no signs of hardware pull-out, however, the reconstruction of the fractured vertebral was unacceptable, the height of the vertebral just increased from 35 and 40% to 70% in the anterior and middle portion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s revision surgery also confirmed that this combined anterior-posterior approach was effective to achieve decompression. Screw loosening was considered to be related to severe osteoporosis in such patients [ 10 ] and stress concentration of internal fixation because of multi-segment cervical fusion. Therefore, preoperative radiography should be carefully evaluated, and postoperative external fixation measures should be taken forcefully without delay.…”
Section: Discussionmentioning
confidence: 99%